1976
DOI: 10.1002/eji.1830060113
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the maturation of thymus stem cells The effects of catecholamines, histamine and peptide hormones on the expression of T cell alloantigens

Abstract: Studies have been performed in order to investigate the effects of catecholamines. histamine, peptide hormones and various other agents known to increase cellular adenosine 3':5'-cyclic monophosphate (cAMP) levels on the expression of Thy-1 and TL antigens on 14-day fetal thymic stem cells. It has been shown that the proportions of Thy-1 and TL positive cells, as detected by dye exclusion cytotoxicity tests, can be significantly increased by some of these agents and that these effects may be inhibited by beta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…Early studies in the 1970s and 1980s allude to β-AR-induced enhancement of thymocyte differentiation and suppression of thymocyte proliferation in the presence of intact NA innervation [58][59][60][61][62][63]. Isoproterenol exposure in vivo reduces thymic weight and thymocyte number in mice [64].…”
Section: Sympathetic Neurotransmission In the Thymusmentioning
confidence: 99%
“…Early studies in the 1970s and 1980s allude to β-AR-induced enhancement of thymocyte differentiation and suppression of thymocyte proliferation in the presence of intact NA innervation [58][59][60][61][62][63]. Isoproterenol exposure in vivo reduces thymic weight and thymocyte number in mice [64].…”
Section: Sympathetic Neurotransmission In the Thymusmentioning
confidence: 99%
“…Tracing analysis indicates that thymic sympathetic outflow directly starts in neurons from the thoracic spinal cord, brainstem, caudal raphe nucleus, and hypothalamus (Trotter et al, 2007). Furthermore, the neurotransmitter norepinephrine (Singh and Owen, 1976;Felten et al, 1987;Morale et al, 1992;Tsao et al, 1996;Kurz et al, 1997;von Patay et al, 1998von Patay et al, , 1999 is found in the thymus, and thymic cells express both ␤1-and ␤2-adrenergic receptors (Morale et al, 1992;Kurz et al, 1997;von Patay et al 1999) able to modulate maturation of T precursor cells and influence the thymic microenvironment. Thus, a link between the brain and the thymus is supported at different levels.…”
Section: Autonomic Denervation Of the Gld Thymusmentioning
confidence: 99%
“…These include studies in which the appearance ofThy-1 has been a major factor in concluding that differentiation to a "'prothymocyte" or T cell has been induced in vitro (e.g., see refs. [20][21][22]. Although in some cases additional T-cell markers (e.g., TL or Lyt) have been monitored, the possibility that these antigens too occur on activated hemopoietic progenitor cells should be formally excluded.…”
mentioning
confidence: 99%